Kekerasan Seksual di kampus dalam Perspektif Islam - Utami, Retno Rahayu; Aditia Muhammad Noor; Faisal Amru, Muhamad; Aulial Andini, Allysai; Athaya Fitriani, Nauza (At-Tuhfah : Jurnal Studi Keislaman, 2024)
This article aims to find out and describe the Islamic perspective on sexual violence on campus, where the problem of sexual violence is often an important issue because it is a complex issue of gender equality, sexual violence concerns various aspects of human life, such as morals, religion, faith, and etc. One of the punishments received by perpetrators of sexual violence is in the form of takzir. Cases of sexual violence are rife on campus so it is necessary to take further action on this matter so that it does not happen again and every student can feel safe wherever they are. Therefore, the purpose of writing this article is to find out the Islamic perspective on sexual violence that often occurs on campus and what solutions we can provide so that cases like this can stop happening. There are 2ifactors that cause sexual violence, namely internal and external factors. As for victims of sexual harassment, especially women, they tend to refuse to have sexual intercourse later when they are married.